2022
DOI: 10.3390/su14052897
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green HRM on Employees’ Eco-Friendly Behavior: The Mediator Role of Organizational Identification

Abstract: This study sought to explore the impact of green human resource management on organizational identification and employees’ eco-friendly behavior, as well as the mediating role of organizational identification in the relationship between green human resource management and employees’ eco-friendly behavior. To achieve the study objectives, a cross-sectional quantitative study was developed, for which the data were obtained through a structured questionnaire containing the measures of the study variables. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 76 publications
(108 reference statements)
1
38
0
2
Order By: Relevance
“…More specifically, green HRM plays a more prominent role in forming a positive relationship between OEC and ES than EP. To some extent, these findings are consistent with the previous results, i.e., [8,43,70], in the mediating effects of the different factors in developing the associations in the other regions. This study's findings demonstrate, also, that green HRM indirectly develops OEC's association with ES and EP.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…More specifically, green HRM plays a more prominent role in forming a positive relationship between OEC and ES than EP. To some extent, these findings are consistent with the previous results, i.e., [8,43,70], in the mediating effects of the different factors in developing the associations in the other regions. This study's findings demonstrate, also, that green HRM indirectly develops OEC's association with ES and EP.…”
Section: Discussionsupporting
confidence: 92%
“…Further, there has been no previous investigation of the combined mediating effect of green HRM and GI with OEC on ES and EP [8,28,36,37,39]. Contextually, despite their apparent relationship in the literature mentioned above, the management of the Saudi Arabian SMEs sector has not paid sufficient attention to these constructs [9,15,[40][41][42][43].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The confirmation of Hypotheses 1 and 3 indicated that green HRM has an effect on organizational identification and job satisfaction (e.g., [76]); that is, management centered on environmental objectives increased employees' identification with organizational values and heightened job satisfaction [77].…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, our results contribute to an expansion of existing knowledge on the relationship between the organizational and individual determinants of extra-role behaviors toward the sustainability of the organization. Accordingly, they indicate that there may be identified with the organization's green values [76], but that this is not enough to advance towards citizenship behaviors. These results seem to point to a logic of action centered on a "winwin" perspective [3], as will be seen below.…”
Section: Discussionmentioning
confidence: 99%